Investigation of the Effect of Coupling Agent on the Properties of Kenaf Fiber/Polypropylene Composites - S.Z.S.M, Zaki; Nurjannah, Salim; N.H.A., Bakar; R., Roslan; N.A., Samah; S.M., Kabeb; S.N., Sarmin (IOP Publishing, 2024)
In a competitive product market, manufacturers ought to utilize eco-friendly materials to reduce the environmental impact of their products. Kenaf (Hibiscus cannabinus) is an annual plant that produces bast fiber and develops rapidly. These fibers have excellent properties and could serve as ideal reinforcing fillers for wood-based products. This study aims to investigate Maleated Polypropylene (MAPP) as a coupling agent for Kenaf fiber (KF)/Polypropylene(PP) composite. Three distinct composites were created using the following ratios: Sample 1 (Kenaf 20g: PP 180g), Sample 2 (Kenaf 10g: PP 180g: MAPP 10g), and Sample 3 (Kenaf 15g: PP 180g: MAPP 5g). All materials are mixed and extruded in a single-screw extruder at 185 to 200 °C at 50 rpm. A granulator is then utilized to palletize the samples. For testing, tensile and impact testing is conducted for mechanical properties, water absorption for physical properties, and Scanning Electron Microscopy (SEM) for morphological characterization. The thermal characteristics of the composites are analyzed using thermogravimetric analysis (TGA). The results indicate that the KF/PP composite with a coupling agent has a higher tensile strength with a value of 29.3 MPa compared to the KF/PP composite without a coupling agent with a value of 22.4 MPa. Water absorption of composite with coupling agent was also less than without coupling agent with a value of 1.05% and 1.31% respectively.